SOME RESULTS OF STUDY ON PRESENT SITUATION OF HOUSEHOLD SOLID WASTE IN HANOI, VIETNAM - To Thi Hai Yen; Pham Thi Thu Ha; Nguyen The Dong; Trinh Van Tuyen; Kosuke Kawai; Saburo Matsui (Universitas Gadjah Mada, 2008)
This paper presents some results on the study of Solid waste generated by households (hereinafter referred to as HSW) in Hanoi city. Compositions of the waste generated from three typical communities and their relationship with family life-style of each community were investigated. Differences among compositions of HSW of three resident groups of different incomes, lifestyles were analyzed. Based on the study results, some measures for better management of HSW and maximum reuse and recycle of HSW were proposed. By this way, the amount of HSW transported to landfill could be reduced and stabilization phase of landfill sites could be shortened.